Battery diaphragm and battery
By using the composite coating on the base film side on the lithium battery separator, combining the layered structure of heat-resistant materials and glue materials, the problem of insufficient adhesive strength of the separator is solved, the diaphragm structure is simplified, the powder drop rate is reduced, and the improvement of the The energy density and safety performance of the battery are achieved.
Patent Information
- Application Number
- CN202411286180.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2024-12-24
AI Technical Summary
The adhesive strength of the existing lithium battery separator is not ideal, resulting in poor interface fit, affecting electrical performance, and frequent powder loss of the diaphragm during production, increasing the risk of short circuit, and the thickness of the separator is not suitable for the cyclic expansion and contraction process of the battery.
The composite coating on the base film side is adopted, the coating includes heat-resistant materials and glue materials, forming a layered structure to meet the specific particle size distribution and coverage, combining inorganic nanoparticles and modified nanofibers to increase the bonding force. It also contains phosphorus-containing compounds, binders and wetting agents, simplifying the coating structure to adapt to the lamination process.
It improves the adhesion of the diaphragm, reduces the powder drop rate of the diaphragm, reduces the accumulation of foreign matter, improves the energy density and safety performance of the battery, and adapts to the hot pressing and transport process of the battery cell.
Smart Images

Figure CN119181932A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of battery materials, and specifically relates to a battery separator and a battery. Background Art
[0002] With the rapid development of the new energy industry in recent years, the demand for batteries has been growing. Lithium batteries have been widely used in electric vehicles, large energy storage power stations, and mobile digital electronic products due to their high energy density and good cycle performance. In the structure of lithium-ion batteries, the diaphragm is one of the key components and is closely related to the safety and performance of the battery. It mainly isolates the positive and negative electrodes to prevent the positive and negative electrodes from directly contacting and short-circuiting, and has a suitable pore size to allow lithium ions to pass through the pores evenly. In order to effectively suppress thermal runaway of the battery, in addition to having good heat resistance and a high membrane rupture temperature, the diaphragm must also have excellent flame retardancy to prevent the combustion of battery materials and improve the spread of battery heat.
[0003] At present, the structure of mass-produced diaphragms is generally a base film + heat-resistant coating + adhesive layer. The heat-resistant coating and the adhesive layer are coated separately. Usually, the heat-resistant coating is coated on one or both sides of the base film, and then the adhesive coating is coated on both sides of the diaphragm. The coating process is many times, and the material BOM and processing costs are high. In addition, during the battery production process, the diaphragm powder falls off frequently, and the dust particles agglomerate in size and become larger. They are introduced into the battery, posing a short circuit risk. In addition, during the long cycle of the battery, the pole piece repeatedly expands and contracts to generate stress. The bonding force between the diaphragm and the pole piece cannot meet the demand, and the interface fits poorly, resulting in increased interface impedance, affecting electrical performance. Summary of the invention
[0004] The present application provides a battery separator and a battery, aiming to solve the problem of unsatisfactory adhesion of existing battery separators.
[0005] A first embodiment of the present application provides a battery separator, comprising a base film and a composite coating disposed on one side of the base film;
[0006] The composite coating comprises a heat-resistant material and an adhesive material. The heat-resistant material forms a layered structure and adheres to the base film. The adhesive material is distributed in the layered structure and satisfies:
[0007] 1.6≤D 50 / H≤4.3,2.2≤D 90 / H≤6.6;
[0008] Among them, D 50 D is the particle size corresponding to the cumulative particle size distribution of the adhesive material reaching 50%, in μm; 90 is the particle size corresponding to when the cumulative particle size distribution in the adhesive material reaches 90%, in μm; H is the thickness of the layered structure, in μm.
[0009] In some embodiments, the air permeability of the base film is 50 to 300 s / 100 cc.
[0010] In some embodiments, the base film has micropores, and the micropores, the heat-resistant material, and the adhesive material satisfy the following conditions:
[0011] F=P ave / P max ×(0.1~0.5)×100%;
[0012] Wherein, F is the coverage of the adhesive material in the heat-resistant material, P ave is the average pore size of the micropores, in nm; P max is the maximum pore size of the micropores, in nm.
[0013] In some embodiments, the base film has a thickness of 3 to 20 μm.
[0014] In some embodiments, the base film has micropores, the pore diameter of the micropores is 15-110 nm, and the porosity of the base film is 25-70%.
[0015] In some embodiments, the particle size of the glue material satisfies: 3.5 μm ≤ D 50 ≤6.8μm, 5.8μm≤D 90 ≤10μm.
[0016] In some embodiments, the thickness of the layered structure satisfies: 1 μm≤H≤3 μm.
[0017] In some embodiments, the coverage of the adhesive material in the heat-resistant material satisfies: 2%≤F≤16%.
[0018] In some embodiments, the micropores satisfy: 25nm≤P ave ≤60nm, 45nm≤P max ≤110nm.
[0019] In some embodiments, the mass ratio of the heat-resistant material to the adhesive material is 20:(1-4).
[0020] In some embodiments, the heat-resistant material includes at least one of inorganic nanoparticles and modified nanofibers, wherein the modified nanofibers contain lithium and fluorine;
[0021] Wherein, the particle size of the inorganic nanoparticles is 50 to 1200 nm.
[0022] In some embodiments, the modified nanofibers have a diameter of 3 to 50 nm and a length of 200 to 1000 nm.
[0023] In some embodiments, in the modified nanofibers, the mass percentage of lithium element is 0.2-0.7%, and the mass percentage of fluorine element is 0.5-1.2%.
[0024] In some embodiments, the inorganic nanoparticles include at least one of aluminum oxide, boehmite, barium sulfate, titanium dioxide, aluminum nitride, magnesium hydroxide, and barium titanate.
[0025] In some embodiments, the modified nanofibers include at least one of pre-lithiated and pre-fluorinated cellulose nanofibers, meta-aramid nanofibers, para-aramid nanofibers, polyimide nanofibers, and polyamide nanofibers.
[0026] In some embodiments, the mass ratio of the inorganic nanoparticles to the modified nanofibers is (5-10):1.
[0027] In some embodiments, the glass transition temperature of the adhesive material is -30 to 80°C.
[0028] In some embodiments, the adhesive material is at least one of a polyacrylate compound and a polyolefin compound.
[0029] In some embodiments, the composite coating further comprises a phosphorus-containing compound, a binder, a wetting agent, and a dispersant;
[0030] The composite coating comprises, by mass percentage:
[0031] 75-90% heat-resistant materials;
[0032] 5-18% of adhesive material;
[0033] 1.1-1.8% phosphorus compounds;
[0034] 3.5-6.3% binder;
[0035] 0.25-0.65% wetting agent;
[0036] 0.04~0.1% dispersant.
[0037] In some embodiments, the phosphorus-containing compound includes at least one of trimethyl phosphate, triethyl phosphate, triphenyl phosphate, tributyl phosphate, hexamethylphosphazene, tris(2,2,2-trifluoroethyl)phosphate, tris(2,2,2-trifluoroethyl)methyl phosphate, and (2,2,2-trifluoroethyl)diethyl phosphate.
[0038] The binder includes at least one of polyacrylic acid, polyacrylate and polyacrylamide.
[0039] In some embodiments, the wetting agent includes at least one of a polyether compound and a silicone compound.
[0040] In some embodiments, the dispersant includes at least one of n-butanol, tert-butanol, and ethanol.
[0041] In some embodiments, the binder has a glass transition temperature of 80-190°C.
[0042] A second embodiment of the present application provides a battery, comprising the battery separator in any of the above embodiments.
[0043] The present application provides a battery separator, comprising a base film and a composite coating arranged on one side of the base film; the composite coating comprises a heat-resistant material and a glue material, the heat-resistant material forms a layered structure and adheres to the base film, the glue material is distributed in the layered structure, and satisfies: 1.6≤D 50 / H≤4.3,2.2≤D 90 / H≤6.6; where D 50 It is the particle size corresponding to the cumulative particle size distribution of the rubber material reaching 50%, in μm; D 90 is the particle size corresponding to 90% of the cumulative particle size distribution in the adhesive material, in μm; H is the thickness of the layered structure, in μm. The battery separator provided in the present application effectively simplifies the separator coating by combining the heat-resistant material with the adhesive material to form a composite coating. At the same time, by limiting the relationship between the particle size in the adhesive material and the thickness of the heat-resistant material, the composite coating has good adhesion, and thus can satisfy the requirement of coating the mixed coating only on one side of the base film, further simplifying the overall structure of the separator, adapting the lamination process and the winding process, and both can meet the requirements of the hot pressing and transportation process of the battery cell. After the simplification of the separator, the powder loss rate of the separator can be reduced, effectively reducing the accumulation of foreign matter piercing the separator, and improving the short circuit rate; at the same time, the thickness of the separator is thinned, which increases the energy density of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] The technical solution and other beneficial effects of the present application will be made apparent by describing in detail the specific implementation methods of the present application in conjunction with the accompanying drawings.
[0045] Figure 1 A schematic diagram of the structure of a battery separator provided in an embodiment of the present application;
[0046] Figure 2 A schematic diagram of the structure of a battery separator provided as a comparative example of the present application;
[0047] Reference numerals:
[0048] 10-base film, 20-composite coating, 30-heat-resistant layer, 40-adhesive layer. DETAILED DESCRIPTION
[0049] The technical solutions in the embodiments of the present application will be described clearly and completely below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present application.
[0050] In the description of the present application, it should be noted that, unless otherwise clearly specified and limited, the terms "connected" and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection, an electrical connection, or can communicate with each other; it can be directly connected, or indirectly connected through an intermediate medium, or indirectly connected through a pipe or pipeline, and it can be the internal connection of two elements or the interaction relationship between two elements. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to the specific circumstances. In the description of the present application, the meaning of "multiple" is two or more, unless otherwise clearly and specifically defined. In addition, the terms "first" and "second" are used for descriptive purposes only, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Therefore, the features defined as "first" and "second" can explicitly or implicitly include one or more features.
[0051] The first embodiment of the present application provides a battery separator, such as Figure 1 As shown, it includes a base film 10 and a composite coating 20 disposed on one side of the base film 10;
[0052] The composite coating 20 includes a heat-resistant material and an adhesive material. The heat-resistant material forms a layered structure and adheres to the base film 10. The adhesive material is distributed in the layered structure to meet the following conditions:
[0053] 1.6≤D 50 / H≤4.3,2.2≤D 90 / H≤6.6;
[0054] Among them, D 50 It is the particle size corresponding to the cumulative particle size distribution of the rubber material reaching 50%, in μm; D 90 It is the particle size corresponding to 90% of the cumulative particle size distribution in the rubber material, in μm; H is the thickness of the layered structure, in μm.
[0055] Understandably, D 50 / H can be any value among 1.6, 2.2, 2.8, 3.4, 4.0, 4.3 or a range between any two values. 90The value of / H can be any of 2.2, 3.1, 4.0, 4.9, 5.8, 6.6 or a range between any two values. By combining the heat-resistant material with the adhesive material to form a composite coating, the diaphragm coating is effectively simplified. At the same time, by limiting the relationship between the particle size in the adhesive material and the thickness of the heat-resistant material, the composite coating has good adhesion, so that it can meet the requirement of coating the mixed coating only on one side of the base film, further simplifying the overall structure of the diaphragm, adapting the stacking process and the winding process, and both can meet the battery cell hot pressing and transportation processes. After the simplification of the diaphragm, the powder loss rate of the diaphragm can be reduced, effectively reducing the accumulation of foreign matter piercing the diaphragm and improving the short circuit rate; at the same time, the thickness of the diaphragm is thinned, which increases the energy density of the battery.
[0056] In some embodiments, the air permeability of the base film 10 is 50 to 300 s / 100 cc.
[0057] It is understood that the air permeability of the base film 10 (unit: s / 100cc) can be any value among 50, 100, 150, 200, 250, 300 or a range between any two values. When the air permeability of the base film 10 meets the above range, the battery DCR can be prevented from increasing too much, resulting in the problem of rapid cycle attenuation.
[0058] In some embodiments, the base film 10 has micropores, and the micropores, heat-resistant material, and adhesive material satisfy the following requirements:
[0059] F=P ave / P max ×(0.1~0.5)×100%;
[0060] Among them, F is the coverage of the adhesive material in the heat-resistant material, P ave is the average pore size of the micropores, in nm; P max is the maximum pore size of the micropores, in nm.
[0061] When the coverage of the adhesive material in the heat-resistant material and the pore size of the micropores in the base film 10 satisfy the above relationship, the pore blocking effect of the adhesive material is small, the composite coating has a small increase in air permeability, and does not affect the adhesion and heat resistance of the diaphragm. This ensures that the prepared diaphragm has excellent lithium ion conductivity, suitable adhesion and heat resistance, and the formed battery has good electrical performance and safety performance.
[0062] In some embodiments, the base film 10 has a thickness of 3 to 20 μm.
[0063] It can be understood that the thickness of the base film 10 (unit: μm) can be any value among 3, 5, 10, 15, 20 or a range between any two values.
[0064] In some embodiments, the base film 10 has micropores, the pore diameter of the micropores is 15-110 nm, and the porosity of the base film 10 is 25-70%.
[0065] It is understood that the pore size of the micropores (unit: nm) can be any value among 15, 30, 50, 80, 100, 110 or a range between any two values; the porosity of the base film 10 can be any value among 25%, 35%, 50%, 60%, 70% or a range between any two values. When the pore size and porosity of the base film 10 meet the above ranges, it has good lithium ion permeability, which can further ensure that the battery cell formed by the separator with the base film 10 has good electrical performance.
[0066] In some embodiments, the particle size of the glue material satisfies: D 10 ≥1.5um, 3.5μm≤D 50 ≤6.8μm, 5.8μm≤D 90 ≤10μm, D 99 ≤12.5μm.
[0067] Among them, D 10 D is the particle size corresponding to the cumulative particle size distribution of the rubber material reaching 10%; 99 It is the particle size corresponding to the cumulative particle size distribution in the glue material reaching 99%. It can be understood that D 50 The value (unit: μm) can be any value among 3.5, 4, 4.5, 5, 5.5, 6, 6.8 or a range between any two values. When the particle size of the adhesive material meets the above value range, the adhesive material can be more stably distributed in the heat-resistant material and achieve a better bonding effect.
[0068] In some embodiments, the thickness of the layered structure satisfies: 1 μm≤H≤3 μm.
[0069] It is understandable that the value of the thickness H of the layered structure (unit: μm) can be any value among 1, 1.5, 2, 2.5, 3, or a range between any two values. When the thickness of the layered structure formed by the heat-resistant material meets the above value range, it can ensure that the heat-resistant material has sufficient heat-resistant strength on the basis of the overall thin thickness of the composite coating 20.
[0070] In some embodiments, the coverage of the adhesive material in the heat-resistant material satisfies: 2%≤F≤16%.
[0071] It can be understood that the coverage rate of the adhesive material in the heat-resistant material can be any value among 2%, 6%, 10%, 14%, 16%, or a range between any two values.
[0072] Based on the above embodiment, the coating amount of the adhesive material on the surface of the base film 10 is 0.13-0.55 g / m 2 .
[0073] In some embodiments, the micropores satisfy: P min ≥15nm, 25nm≤P ave ≤60nm, 45nm≤P max ≤110nm.
[0074] Among them, P min is the minimum diameter of the micropores. It is understood that the average diameter of the micropores (unit: nm) can be any value among 25, 30, 35, 40, 45, 50, 55, 60 or a range between any two values. The coverage of the adhesive material in the heat-resistant material and the diameter of the micropores in the base film 10 can both affect the air permeability of the base film 10. When the coverage of the adhesive material in the heat-resistant material and the diameter of the micropores in the base film 10 meet the above range of values, the battery cell formed by the diaphragm of the base film 10 can be further promoted to have better safety and electrical performance.
[0075] In some embodiments, the mass ratio of the heat-resistant material to the adhesive material is 20:(1-4).
[0076] It can be understood that the mass ratio of the heat-resistant material to the adhesive material can be any value among 20:1, 20:2, 20:3, 20:4 or a range between any two values.
[0077] In some embodiments, the heat-resistant material includes at least one of inorganic nanoparticles and modified nanofibers, wherein the modified nanofibers contain lithium and fluorine.
[0078] The nanofibers are modified with lithium and low surface energy to improve the ionic conductivity of the diaphragm, with the conductivity being greater than 1.5 mS / cm (25°C). Compared with the unmodified nanofiber diaphragm, the moisture content of the diaphragm can be reduced by 500 to 1000 ppm.
[0079] The particle size of the inorganic nanoparticles is preferably 50 to 1200 nm, more preferably 200 to 800 nm.
[0080] It is understood that the particle size of the inorganic nanoparticles (unit: nm) can be any value among 200, 400, 600, 800 or a range between any two values. When the particle size of the inorganic nanoparticles meets the above value range, the inorganic nanoparticles and the modified nanofibers can be evenly dispersed when preparing the slurry.
[0081] In some embodiments, the modified nanofibers have a diameter of 3 to 50 nm and a length of 200 to 1000 nm.
[0082] It can be understood that the diameter value (unit: nm) of the modified nanofiber can be any value among 3, 10, 20, 30, 40, 50 or a range between any two values, and the length value (unit: nm) can be any value among 200, 400, 600, 800, 1000 or a range between any two values. When the diameter and length of the modified nanofiber meet the above value ranges, the heat resistance of the finished film can be improved.
[0083] In some embodiments, in the modified nanofibers, the mass percentage of lithium element is 0.2-0.7%, and the mass percentage of fluorine element is 0.5-1.2%.
[0084] In some embodiments, the inorganic nanoparticles include at least one of aluminum oxide, boehmite, barium sulfate, titanium dioxide, aluminum nitride, magnesium hydroxide, and barium titanate.
[0085] In some embodiments, the modified nanofibers include at least one of pre-lithiated and pre-fluorinated cellulose nanofibers, meta-aramid nanofibers, para-aramid nanofibers, polyimide nanofibers, and polyamide nanofibers.
[0086] When the inorganic nanoparticles and the modified nanofibers are mixed and used, the mass ratio of the inorganic nanoparticles to the modified nanofibers is (5-10):1.
[0087] It can be understood that the mass ratio of the inorganic nanoparticles to the modified nanofibers can be any value of 5:1, 6:1, 7:1, 8:1, 9:1, 10:1 or a range between any two values.
[0088] In some embodiments, the glass transition temperature of the glue material is -30 to 80°C.
[0089] It can be understood that the glass transition temperature of the adhesive material (unit: ° C) can be any value among -30, -10, 0, 20, 40, 60, 80 or a range between any two values. When the glass transition temperature of the adhesive material meets the above range, it can give the diaphragm the characteristics of room temperature or low temperature bonding, which can reduce the hot pressing temperature and reduce the process energy consumption.
[0090] In some embodiments, the adhesive material is at least one of polyacrylate compounds (such as large-particle PMMA) and polyolefin compounds (such as polyethylene microspheres and polypropylene microspheres).
[0091] The surface of the above-mentioned adhesive material is modified by some self-crosslinking groups, and self-crosslinking occurs at about 100°C, which can be used for secondary bonding. Usually, the battery cell is baked at 100±5°C. Based on the characteristics of the adhesive material, the hardness of the battery cell can be further improved after baking.
[0092] In some embodiments, the composite coating 20 further includes a phosphorus-containing compound, and the mass percentage of the phosphorus-containing compound in the composite coating 20 is 1.1-1.8%.
[0093] Based on the above embodiments, the phosphorus-containing compound can be a simple phosphorus-containing compound or a phosphorus-fluorine composite compound, such as trimethyl phosphate, triethyl phosphate, triphenyl phosphate, tributyl phosphate, hexamethylphosphazene, tris(2,2,2-trifluoroethyl) phosphate (TMP), tris(2,2,2-trifluoroethyl) methyl phosphate (BMP), (2,2,2-trifluoroethyl) diethyl phosphate (TDP) or one or more combinations thereof. When the battery is subjected to external impact, extrusion, overheating or overcharging, the electrolyte in the lithium battery is prone to release oxygen, resulting in a chain reaction of hydrogen free radicals, which ultimately causes the battery to burn, ignite and explode. When heated, the phosphorus-containing compound in the diaphragm will gasify and decompose to release flame-retardant free radicals P·, which can capture hydrogen free radicals H· in the electrolyte system, prevent hydrocarbons from chain reactions, and thus prevent the electrolyte from burning. When the battery has thermal runaway, the temperature of the battery core can be reduced, or even thermal runaway will not occur, preventing the battery from igniting and exploding.
[0094] In some embodiments, the composite coating 20 further includes a binder, a wetting agent, and a dispersant; wherein the glass transition temperature of the binder is 80-190°C.
[0095] It can be understood that the glass transition temperature of the adhesive (unit: ° C) can be any value among 80, 100, 120, 140, 160, 190 or a range between any two values.
[0096] The binder can be one or more combinations of polyacrylic acid, polyacrylate and polyacrylamide; the wetting agent can be one or more combinations of polyether and siloxane; the dispersant can be one or more combinations of n-butanol, tert-butanol or ethanol.
[0097] In some embodiments, the composite coating 20 may include the following components by mass:
[0098] Heat-resistant materials: 75-90%;
[0099] Adhesive material: 5-18%;
[0100] Phosphorus compounds: 1.1-1.8%;
[0101] Binder: 3.5-6.3%;
[0102] Wetting agent: 0.25-0.65%;
[0103] Dispersant: 0.04~0.1%.
[0104] When the composite coating 20 has the components in the above formula, the composite coating 20 can have good comprehensive performance in terms of heat resistance, flame retardancy, strength, adhesion, etc.
[0105] A second embodiment of the present application provides a battery, comprising the battery separator in any of the above embodiments.
[0106] The following is a description of a battery separator and a battery provided by the present application in combination with specific embodiments:
[0107] Example 1
[0108] Example 1 provides a battery separator, and a coating slurry is prepared according to the following formula:
[0109] Heat-resistant materials: boehmite and modified meta-aramid nanofibers, 83%;
[0110] Adhesive material: polyacrylate, 10.2%;
[0111] Phosphorus compounds: trimethyl phosphate, 1.5%;
[0112] Binder: polyacrylate, 4.8%;
[0113] Wetting agent: polyether compound, 0.45%;
[0114] Dispersant: n-butanol, 0.05%.
[0115] The uniformly mixed coating slurry is applied to one side of the base film 10, such as Figure 1 As shown, a composite coating 20 is formed on one side of the base film 10, and the base film 10 and the composite coating 20 constitute a battery separator.
[0116] The battery separator prepared by the above method is used to prepare a battery, which specifically includes the following steps:
[0117] 1) Preparation of positive electrode sheet: lithium iron phosphate, conductive agent, binder, etc. are used to prepare slurry, which is coated on carbon-coated aluminum foil and processed to obtain positive electrode sheet, with the positive electrode accounting for 96.7% of the coating.
[0118] 2) Preparation of negative electrode sheet: artificial graphite, conductive agent, adhesive, thickener and other materials are used to prepare slurry, which is then coated on copper foil to form a negative electrode sheet after treatment. The negative electrode accounts for 96.1% of the coating.
[0119] 3) The positive and negative electrode sheets and the diaphragm are shaped by lamination or winding process to obtain an electrode group, in which the diaphragm coating faces the positive electrode. Then, the electrode group with a certain hardness is obtained by hot pressing. The hot pressing parameters are: hot pressing temperature 35-90℃, surface pressure 0.8-3MPa, time 30-150s. The hot pressed electrode group is subjected to hipot short circuit test.
[0120] 4) Packaging, baking, and liquid injection: The prepared electrode group is packaged in a square shell form, the packaged battery cell is placed in an oven, baked at 100±5℃ for 10±2h, and then the electrolyte is injected.
[0121] 5) Pre-charging and formation: After the standing period is completed, the battery cell is pre-charged, formed and capacity divided to obtain the battery of the present invention.
[0122] Example 2
[0123] Example 2 provides a battery separator, and a coating slurry is prepared according to the following formula:
[0124] Heat-resistant materials: boehmite and modified meta-aramid nanofibers, 84.5%;
[0125] Adhesive material: polyacrylate compound, 10.2%;
[0126] Binder: polyacrylate, 4.8%;
[0127] Wetting agent: polyether compound, 0.45%;
[0128] Dispersant: n-butanol, 0.05%.
[0129] The uniformly mixed coating slurry is applied to one side of the base film 10, such as Figure 1 As shown, a composite coating 20 is formed on one side of the base film 10, and the base film 10 and the composite coating 20 constitute a battery separator.
[0130] Subsequently, a battery was prepared according to the same procedure as in Example 1.
[0131] Embodiments 3 to 6
[0132] The preparation methods of the battery separators and batteries provided in Examples 3 to 6 are consistent with those in Example 1, with the only difference being the adjustment of the components of the composite coating 20, as shown in Table 1 for details.
[0133] Comparative Example 1
[0134] Commercial 9+2+3+3 single-sided ceramic, double-sided sprayed PVDF diaphragm, such as Figure 2 As shown, it includes a base film 10, a heat-resistant layer 30, and an adhesive layer 40, wherein the heat-resistant layer 30 is arranged on one side of the base film 10, and the adhesive layer 40 is respectively arranged on the side of the base film 10 away from the heat-resistant layer 30, and the side of the heat-resistant layer 30 away from the base film 10.
[0135] The specific preparation method of the battery prepared using the diaphragm is consistent with that of Example 1.
[0136] Comparative Examples 2 to 5
[0137] The preparation methods of the battery separators and batteries provided in Comparative Examples 2 to 5 are consistent with those in Example 1, with the only difference being the adjustment of the components of the composite coating 20, as shown in Table 1 for details.
[0138] Table 1
[0139]
[0140]
[0141] The following tests were performed on the diaphragm proposed in the present invention: thermal shrinkage at 150°C, film rupture temperature, limiting oxygen index, hot nail puncture area, coating powder loss rate, adhesion between fresh diaphragms, and adhesion between diaphragms after baking at 100°C.
[0142] The following tests were performed on the battery pole prepared by the simplified high flame retardant separator of the coating of the present invention: extreme hot box test, and heat spread test at room temperature and 60°C.
[0143] The test results are shown in Table 2.
[0144] Table 2
[0145]
[0146]
[0147] Through the analysis of the embodiments and comparative examples, the present invention only needs to coat one side of the base film with the coating described in the above scheme, that is, the coating is simplified, so that the thermal shrinkage at 150°C can meet <3%, the film breaking temperature is 160-230°C, and the coating powder loss rate is <1.5%. In addition, the diaphragm and the diaphragm have adhesion after hot pressing at room temperature and 90°C, respectively, with a ratio of 1.31N / m and 7.24N / m. More specifically, after baking at 100°C, the adhesion of the diaphragm can be increased by 40%, with a typical value of 10.18N / m. This feature is not possessed by the PVDF coated diaphragm used in comparative example 1. This feature can not only reduce the hot pressing temperature, realize the hot pressing of the pole group at low temperature or even room temperature, reduce energy consumption costs, and reduce the coating on one side of the diaphragm, reducing manufacturing costs. At the same time, after the battery cell is baked, the diaphragm coating is secondary viscous, the adhesion is improved, and the hardness of the battery cell is further improved. The limiting oxygen index of the diaphragm prepared using flame retardant additives is increased from 15.3 to 27.1% compared with that of the diaphragm without flame retardant additives. The hot nail puncture area is 0.6-1.3mm 2 . The battery proposed by the present invention can pass the 220°C hot box test and the normal temperature / high temperature heat spread safety test. In comparative example 1, the 9+2+3+3 diaphragm has poor heat resistance and can only pass the 130°C hot box test, but fails the heat spread test; in Example 2, since no flame retardant additives are added, the limiting oxygen index of the diaphragm is lower than that of the embodiment, and it only passes the 150°C hot box test and the normal temperature heat spread test, but fails the high temperature heat spread test.
[0148] The above is a detailed introduction to a battery separator and a battery provided in the embodiments of the present application. Specific examples are used in the present application to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the technical solutions and core ideas of the present application. Ordinary technicians in this field should understand that they can still modify the technical solutions recorded in the aforementioned embodiments, or replace some of the technical features therein with equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present application.
Claims
1. A battery separator, characterized in that: It includes a base film and a composite coating disposed on one side of the base film; The composite coating comprises a heat-resistant material and an adhesive material. The heat-resistant material forms a layered structure and adheres to the base film. The adhesive material is distributed in the layered structure and satisfies: 1.6≤D 50 / H≤4.3,2.2≤D 90 / H≤6.6; Among them, D 50 D is the particle size corresponding to the cumulative particle size distribution of the adhesive material reaching 50%, in μm; 90 is the particle size corresponding to when the cumulative particle size distribution in the adhesive material reaches 90%, in μm; H is the thickness of the layered structure, in μm.
2. A battery separator according to claim 1, characterized in that: The air permeability of the base film is 50 to 300 s / 100 cc; and / or, The base film has micropores, and the micropores, the heat-resistant material, and the adhesive material satisfy the following requirements: F=P ave / P max ×(0.1~0.5)×100%; Wherein, F is the coverage of the adhesive material in the heat-resistant material, P ave is the average pore size of the micropores, in nm; P max is the maximum pore size of the micropores, in nm.
3. A battery separator according to claim 1 or 2, characterized in that: The thickness of the base film is 3 to 20 μm; and / or, The base film has micropores, the pore diameter of the micropores is 15-110 nm, and the porosity of the base film is 25-70%.
4. A battery separator according to claim 1 or 2, characterized in that: The particle size of the glue material satisfies: 3.5 μm ≤ D 50 ≤6.8μm, 5.8μm≤D 90 ≤10μm; and / or, The thickness of the layered structure satisfies: 1 μm≤H≤3 μm; and / or, The coverage of the adhesive material in the heat-resistant material satisfies: 2%≤F≤16%; and / or, The micropores satisfy: 25nm≤P ave ≤60nm, 45nm≤P max ≤110nm; and / or, The mass ratio of the heat-resistant material to the adhesive material is 20:(1-4).
5. A battery separator according to claim 1, characterized in that: The heat-resistant material includes at least one of inorganic nanoparticles and modified nanofibers, and the modified nanofibers contain lithium and fluorine; Wherein, the particle size of the inorganic nanoparticles is 50 to 1200 nm; and / or, The modified nanofiber has a diameter of 3 to 50 nm and a length of 200 to 1000 nm; and / or, In the modified nanofiber, the mass percentage of lithium element is 0.2-0.7%, and the mass percentage of fluorine element is 0.5-1.2%.
6. A battery separator according to claim 5, characterized in that: The inorganic nanoparticles include at least one of aluminum oxide, boehmite, barium sulfate, titanium dioxide, aluminum nitride, magnesium hydroxide and barium titanate; and / or, The modified nanofibers include at least one of pre-lithiated and pre-fluorinated cellulose nanofibers, meta-aramid nanofibers, para-aramid nanofibers, polyimide nanofibers and polyamide nanofibers; and / or, The mass ratio of the inorganic nanoparticles to the modified nanofibers is (5-10):
1.
7. A battery separator according to claim 1, characterized in that: The glass transition temperature of the adhesive material is -30 to 80°C; and / or, The adhesive material is at least one of a polyacrylate compound and a polyolefin compound.
8. A battery separator according to claim 1, characterized in that: The composite coating also includes a phosphorus-containing compound, a binder, a wetting agent and a dispersant; The composite coating comprises, by mass percentage: 75-90% heat-resistant materials; 5-18% of adhesive material; 1.1-1.8% phosphorus compounds; 3.5-6.3% binder; 0.25-0.65% wetting agent; 0.04~0.1% dispersant.
9. A battery separator according to claim 8, characterized in that: The phosphorus-containing compound comprises at least one of trimethyl phosphate, triethyl phosphate, triphenyl phosphate, tributyl phosphate, hexamethylphosphazene, tris(2,2,2-trifluoroethyl)phosphate, tris(2,2,2-trifluoroethyl)methylphosphate, and (2,2,2-trifluoroethyl)diethylphosphate; and / or, The binder comprises at least one of polyacrylic acid, polyacrylate and polyacrylamide; and / or, The wetting agent comprises at least one of a polyether compound and a silicone compound; and / or, The dispersant comprises at least one of n-butanol, tert-butanol and ethanol; and / or, The glass transition temperature of the binder is 80-190°C.
10. A battery, characterized in that: The invention comprises the battery separator according to any one of claims 1 to 9.
Citation Information
Patent Citations
Battery diaphragm and battery
CN115275524A
Lithium ion battery diaphragm, preparation method thereof and lithium ion battery
CN117977102A
Cited By
Battery separator and battery
WO2026056538A1
